The Role of Judiciary in Environmental Protection: A Review of Key Cases from Pakistan judiciary - Muhammad Abbas Khan, (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
Environmental challenges, including deforestation, groundwater depletion, and pollution, have become critical concerns in Pakistan, threatening public health, biodiversity, and sustainable development. In response, the judiciary has emerged as a pivotal institution in addressing gaps in environmental governance. The leading and landmark judgment set the principle the public interest litigation under the constitutional article 184(3) and also define the article 9 & 14 related to life and dignity of human. While also added the article 9A in the twenty-sixth amendment to clean and healthy environment. This paper provides a comprehensive review of landmark cases, including Shehla Zia v. WAPDA (PLD 1994 SC 693), which demonstrate the judiciary's proactive role in environmental protection. In Shehla Zia v. WAPDA, the Supreme Court expanded the constitutional right to life under Article 9 to include a clean and healthy environment, laying the foundation for environmental jurisprudence in Pakistan. The Sheikh Asim Farooq case addressed the alarming rate of deforestation, which has reduced Pakistan’s forest cover to just 1.9%, one of the lowest globally. The Lahore High Court directed the implementation of national forestry policies, applying the Public Trust Doctrine to treat forests as a shared public resource. The court underscored the importance of sustainable development, biodiversity conservation, and ecosystem services such as carbon sequestration and water filtration.